New possibilities in treatment of chronic urinary tract infections—vaccines, autovaccines and beta glucans - Josef Richter; Vaclav Vetvicka; Karola Haasova; Romana Mikesova; Ivana Stiborova; Vlastimil Kral (临床与病理杂志; 卷 41, 编号 9 (9 2021), 2021)
Background: Repeated infections of urinary tract manifest an increasing trend and became the most common infection in developed world. In addition, currently common increase in resistant microbes including uropathogens underlines the need for new ways of urinary tract infection (UTI) treatment. One of the possibilities is vaccination. However, commercially available bacterial vaccines are not always reliable, leading to the proposition of using autovaccines prepared from uropathogens of individual patients. It is a well-known fact that UTIs are often accompanied by depressed immunity. Methods: To respond to both problems, we tried to use yeast-derived, insoluble beta glucans for restoration of depressed immune system and acceleration of the effects of autovaccines. In all patients we repeatedly tested bacterial load in urine. In addition, from the same samples we measured the levels of inflammatory proteins, albumin, orosomukoid, IgA, C-reactive protein. Complex evaluation of inflammatory response and cellular immunity in blood was performed, too. Results: Immediately after application of the first dose we observed significant improvements of clinical conditions which were persistent throughout the entire study. Conclusions: Beta glucan is optimal addition to autovaccines, as it is natural, active, safe and inexpensive. We propose that the possibility to use beta glucans in application of autovaccines is the first step in preparation of qualitative new type of autovaccines against UTI.